Pars Plana Vitrectomy in Rhegmatogenous Retinal Detachment in Paediatric Patients in Dr. Cipto Mangunkusumo Hospital, Indonesia 2017 - Faresa Hilda; Ari Djatikusumo; Elvioza Elvioza; Gitalisa Andayani Adriono; Anggun Rama Yudantha; Mario Marbungaran Hutapea; Andi Arus Victor (Faculty of Medicine Universitas Indonesia, 2021)
In the past decades, indications for PPV in paediatric patients has been rising with large heterogeneity outcomes among studies. Our objective is to present a pilot descriptive study in Indonesia, regarding pars plana vitrectomy (PPV) success rate in paediatric patients with rhegmatogenous retinal detachment (RRD) in Dr. Cipto Mangunkusumo Hospital (CMH). A retrospective study was conducted on 16 paediatric eyes diagnosed for RRD and treated in CMH during the period of January 2017 to December 2017. A total of 16 RRD eyes were identified in 15 individuals. Majority of the patients were male and were in the age group of 12-18 years. There were 13 patients undergone PPV with or without SB. Functional anatomical success rate was determined from the macula status while functional success rate on final BCVA. Among 16 patients, 14 had constant or increased final BCVA and 11 had reattached macula. The success rate of PPV in terms of anatomical outcome was 11 out of 16 eyes and in functional outcome was 8 out of 16 eyes. Keywords: pars plana vitrectomy, paediatric ophthalmology, rhegmatogenous retinal detachment. Karakteristik dan Hasil Vitrektomi Pars Plana pada Pasien Pediatrik di Divisi Vitreoretina Rumah Sakit Cipto Mangunkusumo Tahun 2017 Abstrak Indikasi tindakan vitrektomi pars plana (PPV) pada pasien pediatrik bertambah secara signifikan dalam beberapa dekade terakhir. Penelitian ini dilakukan sebagai studi awal di Indonesia, terkait tingkat keberhasilan PPV pada pasien anak dengan rhegmatogenous retinal detachment (RRD) khususnya di RS Cipto Mangunkusumo (RSCM). Studi retrospektif dilakukan terhadap 16 mata RRD pada 15 pasien anak di RSCM pada periode Januari 2017 – Desember 2017. Mayoritas pasien merupakan laki-laki dalam kelompok umur 12-18 tahun. Terdapat 13 pasien yang menjalani PPV dengan atau tanpa scleral buckle (SB). Tingkat keberhasilan anatomi dilihat dari status penempelan makula, sementara tingkat keberhasilan fungsional dinilai dari visus akhir. Tingkat keberhasilan anatomi PPV dalam studi ini adalah 11/16 mata, dan tingkat keberhasilan fungsional mencapai 8/16 mata. Kata kunci: vitrektomi pars plana, oftalmologi pediatrik, rhegmatogenous retinal detachment.